2021
DOI: 10.2188/jea.je20200214
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Associated Factors of Pathological Internet Use and Online Risky Behaviors Among Japanese Elementary School Children

Abstract: Background: Little is known about pathological Internet use (PIU) and online risky behaviors among elementary school children. We aimed to investigate the prevalence and factors associated with PIU and online risky behaviors. Methods: A school-based cross-sectional study was conducted in Toyama, Japan in 2018. The study included 13,413 children in the 4th-6th grades (mean, 10.5 years old) from 110 elementary schools (61.1% of elementary schools in Toyama). We assessed PIU using Young's Diagnostic Questionnaire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 28 publications
(53 reference statements)
1
13
0
Order By: Relevance
“…The YDQ might bias the assessment of problematic Internet use, as the tool is somewhat outdated. Although the YDQ is still used in many studies (78)(79)(80)(81), an updated model might be more suitable for the investigation of the Internet use (i.e., the Interaction of Person-Affect-Cognition-Execution model) (82). Finally, the snowball sampling method may result in a biased sample.…”
Section: Discussionmentioning
confidence: 99%
“…The YDQ might bias the assessment of problematic Internet use, as the tool is somewhat outdated. Although the YDQ is still used in many studies (78)(79)(80)(81), an updated model might be more suitable for the investigation of the Internet use (i.e., the Interaction of Person-Affect-Cognition-Execution model) (82). Finally, the snowball sampling method may result in a biased sample.…”
Section: Discussionmentioning
confidence: 99%
“…From 185 in total, 110 elementary schools in Toyama Prefecture (as of 2018, 61.1% of elementary schools in Toyama) joined the survey, responding to a call by the Toyama Prefecture Education Board. In total, 13,413 children in the 4th to 6th grades participated. We distributed an anonymous, self-reported questionnaire to all children in all schools.…”
Section: Participants: Children From the Toyama Safe Internet Use Surveymentioning
confidence: 99%
“… 41 The JIAT has shown good reliability and validity. 17 , 41 , 42 In our study, we considered a JIAT total score of ≥ 50 as IA., and that of < 50 as non-IA.…”
Section: Methodsmentioning
confidence: 99%
“…10 It has become a global problem with a prevalence of 4.2% to 23.7% depending on the age of the participants and various methods of assessing IA. 5,9,[11][12][13][14][15][16][17][18][19][20][21] Family factors, such as growing up with a single parent 22 and low family income, 23,24 are also associated with IA in childhood and adolescence. Recently, some studies suggested IA in adolescence was associated with parental depression.…”
Section: Introductionmentioning
confidence: 99%